The impact of aging on enzyme proteins of rat liver peroxisomes: quantitative analysis by immunoblotting and immunoelectron microscopy - Beier, Konstantin; Völkl, Alfred; Fahimi, H. Dariush (Virchows Archiv. B, Cell pathology including molecular pathology, 1993)
The alterations of hepatic peroxisomes and their enzymes during aging were investigated in male rats. Peroxisomes in the livers of young (2 months) and old (39 months) male Wistar rats were analyzed by morphometry and quantitative immunocytochemistry, as well as by immunoblotting of highly purified peroxisomal fractions. Immunoblots showed that catalase and acyl-CoA oxidase were decreased in peroxisomes of old animals but the trifunctional enzyme, thiolase, and urate oxidase were increased. The morphometrical analysis revealed a heterogeneous distribution of peroxisomes in the liver lobule of the old animals, with a significant elevation of peroxisomal volume density in pericentral over periportal hepatocytes, in contrast to the uniform pattern in the young rats. Furthermore, age-related lobular gradients were also observed by quantitative immunocytochemistry in the peroxisomal concentrations of trifunctional enzyme (central > portal) and, inversely, for catalase (portal > central). Whereas acyl-CoA oxidase was diminished across the liver lobule, the enzyme 3-ketoacyl-CoA thiolase was elevated. These observations show that peroxisomes are significantly altered in aged animals and suggest that these alterations may contribute to the disturbance of lipid metabolism in aged animals. Moreover, the diminution in catalase and the elevation of urate oxidase could contribute to the oxidative stress which is considered to be of fundamental importance in the aging process.
Gesehen am 24.03.2024